Hydrochemistry and isotopic signatures of subpermafrost groundwater discharge along the eastern slope of the Lena River Delta in the Laptev Sea; Journal of Hydrology; Vol. 590 - Charkin A. N. Aleksandr; Pipko I. I. Irina Ivanovna; Pavlova G. Yu. Galina; Dudarev O. V. Oleg Viktorovich; Leusov A. E.; Barabanshchikov Yu. A. Yury; Shcherbakova K. P. Kseniya; Yaroshchuk E. I. Elena; Pugach S. P. Svetlana Petrovna; Gulenko T. Timofey; Goryachev V. A. Vladimir; Semiletov I. P. Igor Petrovich; et al. (2020, 2020)
Title screen